Environmental Sustainability of Triticales to Adverse Environmental Factors - T. A. Aseeva; K. V. Zenkina (Юг России: экология, развитие)
Aim. In regions where farming is risky it is especially important to grow crops with high productivity and optimal adaptability to environmental stress factors. In this regard, the purpose of this study was to determine the environmental sustainability of spring triticale cultivars to the unfavourable environmental factors of the Middle Amur Region.Material and Methods. Many statistical and mathematical methods were used to determine the adaptiveness of potential spring triticale cultivars by yield. As re‐search material, we used 40 cultivars and breeding lines of spring triticale of various ecological and geographical origins.Results. Using cluster analysis, triticale samples were ranked into 5 groups with differing responses to the spectrum of changes in environmental conditions. As a result of this research, it was established that the Skoryi (Russia) and Viktoria (Ukraine) cultivars achieve maximum yield potential as well as having an ability to neutralize the negative impact of soil and climatic factors.Conclusion. The reaction of triticale cultivars to specific vegetation conditions was established. Exemplars of spring triticale with high environmental sustainability, ductility and stability for economic use and further breeding were identified.